2016
DOI: 10.1111/cas.13064
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus selectively blind to signaling lymphocyte activity molecule has oncolytic efficacy against nectin‐4‐expressing pancreatic cancer cells

Abstract: Pancreatic cancer is one of the most intractable cancers and has a devastating prognosis; over the past three decades the 5‐year survival rate has been <10%. Therefore, development of a novel anticancer treatment for pancreatic cancer is a matter of urgency. We previously developed an oncolytic recombinant measles virus (MV), rMV‐SLAMblind, that had lost the ability to bind to its principal receptor, signaling lymphocyte activity molecule (SLAM), but which selectively infected and efficiently killed nectin‐4‐e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Recently Nectin-4 has been reported to be up-regulated in a variety of cancer cells [ 37 , 38 ]. SLAM-blind MV with only R533A substitution has shown oncologic efficacy on lung and pancreatic cancer cells implanted in severe combined immune deficiency (SCID) mice [ 39 , 40 , 41 ]. Table 3 above shows that five amino acid residues in MVH, Asp507, Asp505, Arg533, Arg556, and Asp530, play pivotal roles in binding to SLAM.…”
Section: Resultsmentioning
confidence: 99%
“…Recently Nectin-4 has been reported to be up-regulated in a variety of cancer cells [ 37 , 38 ]. SLAM-blind MV with only R533A substitution has shown oncologic efficacy on lung and pancreatic cancer cells implanted in severe combined immune deficiency (SCID) mice [ 39 , 40 , 41 ]. Table 3 above shows that five amino acid residues in MVH, Asp507, Asp505, Arg533, Arg556, and Asp530, play pivotal roles in binding to SLAM.…”
Section: Resultsmentioning
confidence: 99%
“…The increasing anti-tumour activity of MV-Edm in human adenocarcinoma cells with up-regulated levels of nectin-4 suggested that its expression is correlated with MV-mediated oncolysis [34,35]. …”
Section: Mechanisms Of Specificitymentioning
confidence: 99%
“…In this manner, a miRNA-sensitive measles virus was engineered to target miRNA-7, which is reportedly downregulated in gliomas. While the potency of the oncolytic virus was retained in glioblastoma multiforme xenografts, viral replication was repressed in normal brain tissue, where miRNA-7 is ubiquitously expressed [35]. Moreover, to achieve “detargeting” of multiple vital organs during the systemic administration of oncolytic MV, a triple-miRNA-sensitive virus was developed targeting miRNA-7, miRNA-122 and miRNA148a, commonly expressed in brain tissues, liver and gastrointestinal organs, respectively [57].…”
Section: Engineering Oncolytic Measles Virusmentioning
confidence: 99%
“… 18 , 19 , 20 , 21 We expected that rMV-SLAMblind selectively targets and kills nectin-4 positive tumor cells and demonstrated that rMV-SLAMblind shows anti-tumor effects against various cell lines expressing nectin-4 derived from breast, lung, pancreas, and colorectal cancer. 16 , 22 , 23 , 24 …”
Section: Introductionmentioning
confidence: 99%